Strategi Penyehatan Lingkungan Pemukiman Dalam Pencegahan Penyakit Menular di Indonesia: Literatur Review - Azkiyyatu Zahra; Lilis Lismayanti (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Communicable diseases remain one of the leading public health burdens in Indonesia, particularly in densely populated residential areas and communities with inadequate sanitation. Poor housing conditions including insufficient ventilation, overcrowding, excessive humidity, inadequate lighting, and improper waste and wastewater management have been shown to increase the risk of respiratory infections, diarrhea, and other environment-related diseases. This literature review aims to identify effective environmental health strategies for preventing communicable diseases by synthesizing findings from 11 scientific articles published between 2014 and 2025. The review shows that basic sanitation, indoor air quality, waste management, and the implementation of the Community-Based Total Sanitation (STBM) program are key determinants in reducing disease incidence. Additionally, successful interventions depend heavily on clean and healthy living behaviors (PHBS) and active community participation. These findings highlight the importance of a comprehensive approach that integrates physical environmental improvements, health education, and community empowerment to create healthy settlements and sustainably reduce the risk of communicable diseases.